LA CONSTRUCCIÓN SOCIAL DE LA INFANCIA COSTARRICENSE A INICIOS DEL SIGLO XX - Víquez Jiménez, Paula (2018)
The article summarizes concepts about childhood during the first half of the twentieth century (1900-1950) in the meseta central in Costa Rica. The object of the article is to gather other studies on the topic as to encourage future researched discussed. The article has been divided in three sections: the concept on family, the social universe which surrounded childhood in the period and used sources such as periodicals, national laws and judicial documents.